The Performance of Killer of Gods Band in Semarang (Jurnal Seni Musik, 2023)
Killer of Gods, also known as KOG, has participated in events such as Rockin Solo and Jakarta. The performance style of KOG has successfully created an energetic atmosphere on stage, and captivated the audience with the use of dynamic lighting to enhance the musical experience. This research aimed to explore the performance format of the band Killer of Gods, serving as a reference for musicians and other researchers. The study employed a qualitative method with a phenomenological approach. Data collection was conducted through observation, interviews, and documentation. Data validity was ensured through triangulation. The data analysis process involved data collection, data reduction, data presentation, and drawing conclusions. The performance format of Killer of Gods consists of two aspects, namely composition and presentation. The composition aspect includes rhythm, melody, harmony, instruments, lyrics, arrangement, formation, and performance elements. Meanwhile, the presentation aspect includes stage design, sound system, lighting, makeup, performance timing, and music presentation. In addition, Killer of Gods exclusively performs their own compositions during their music performances.